The review of armed conflict measurement using logit model and probit model in developed and developing countries / Tismazammi Mustafa and Asma' Rashidah Idris - Mustafa, Tismazammi; Idris, Asma' Rashidah (2021)
The purpose of this study is to analyse the armed conflict in both developed and developing countries. The factors of governance, GDP per capita, and other control variables are selected to investigate their effects on armed conflict from 1970 to 2014 in 126 selected countries. By using Logit Model and Probit model, the response of armed conflict on seven measurement of governance namely investment profile, corruption, internal conflict, religious tension, law and order, democratic autocracy, and bureaucracy quality are determined. The population, human capital, and communication are included as control variables. In general, the GDP per capita results revealed that there is a positive relationship with the armed conflict. All governance indicators showed a significant effect on armed conflict except for law and order, and bureaucracy quality